IOT-BASED PROTOTYPE DESIGN OF PT PLN (PERSERO) UP3 PASURUAN'S POST-PAID CUSTOMERS' TEMPORARY ELECTRICITY CIRCUIT BREAKER - Muhammad Rizal Subakti; Akhmad Ahfas (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study addresses the issue of delinquent customer payment behavior, which negatively affects the sustainability of electricity distribution and often necessitates temporary power disconnections by utility providers. Method: A research and development (R&D) approach was employed to design and implement a mobile disconnection system using an Arduino Uno microcontroller, HC-05 Bluetooth module, and an Android-based Bluetooth Controller. Results: Testing demonstrated that the HC-05 module provided an effective connectivity range of up to 4 meters, with an average 0.8-second delay between command transmission from the Android application and execution by the Arduino Uno to cut off electricity. Novelty: The developed IoT-based voltage breaker application significantly improves operational efficiency and service responsiveness for utility officers in handling late-paying customers, thereby enhancing overall utility management and sustainability.